THE TYPES AND FUNCTIONS OF SLANG USED ON TWITTER IN MILLENNIAL ERA - Winarna, Winarna; Tanzila, Sabrina Dhiar (SENTRI: Jurnal Riset Ilmiah, 2024)
This study analyzes the slang used by Twitter users during the Millennial era. The research aims to identify and classify the types of slang words and their functions. It employs qualitative methods, gathering slang data from tweets by Twitter users. The analysis is based on two theories: Abdul Chaer's theory, which categorizes word forms, and Patridge's theory, which explains the functions of slang on Twitter. The study identifies and classifies slang into four categories: basic words, derivative words, acronyms, and abbreviations. In total, 65 slang words were found, including 21 basic words, 6 derivative words, 9 acronyms, and 28 abbreviations. The study also identifies five functions of slang on Twitter: for jokes or fun, to appear unique and modern, to enhance readability and aesthetics, to avoid formalities, and to expand vocabulary.